Integrasi Etika Islam Sebagai Fondasi Moralitas Personal dan Kohesi Sosial dalam Pendidikan Islam - Misrida, Anisa; Inayatillah (TAUJIH: Jurnal Pendidikan Islam, 2025)
This article aims to identify and analyse the basic principles of Islamic ethics in both personal and social dimensions, as well as to examine their practical implementation in contemporary Muslim life. This study applies the library research method, drawing on primary sources such as journals and other literature including articles and e-books. The results indicate that Islamic ethics encompasses two major dimensions. In the personal dimension, Islamic ethics emphasises values such as honesty, trustworthiness, patience, gratitude, and sincerity as the foundation for shaping moral and spiritual character through the process of tazkiyatun nufus. In the social dimension, Islamic ethics highlights the importance of justice, brotherhood (ukhuwah), tolerance, and social responsibility in building a civilised society. In the modern era, Islamic ethical values remain relevant in addressing moral and social crises such as corruption, misinformation, individualism, intolerance, and environmental degradation.